Desain Pembelajaran Alam Semesta Anak TK Menggunakan AR Dengan Tehnik Markerless - R_Soelistijadi R_Soelistijadi; Endang Lestariningsih; Agung Royhans (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
The method of learning the universe at TK Pertiwi Bebengan, Kec. Boja, Kab. Kendal, Central Java is still simple, namely explaining the material by displaying a 2-dimensional still image. This makes students unable to see directly the process of rotation and movement of celestial bodies in the universe. For this reason, it is necessary to create an application that can display the process through 3D animated moving images using Augmented Reality (AR) based technology. The research method used is Prototype, while the architectural design uses UML and software applications using Unity3D, Vuforia, Photoshop CS6 and Blender. The final results of the study are 1) on testing application features made with Unity3D and Vuforia software can run well, 2) on device testing there are 2 out of 4 smartphones that cannot run the application so that a minimum specification of a smartphone is required, 3) on distance testing with a height of 20 cm, it requires the right camera tilt angle, which is between200 to 900. The conclusion of the research is that this application can run well on mobile devices registered in Google's ARCore database and minimum specifications of Android 8.0 Oreo. In addition, it is necessary to pay attention to the right camera tilt angle so that it can display 3D objects.